Studi Perilaku Dan Prestasi Belajar Pendidikan Agama Islam Pada Siswa Autis Di SMP Negeri 5 Surabaya - Hayyan Ahmad Ulul Albab (Faculty of Tarbiyah Universitas Islam Tribakti Lirboyo Kediri, 2018)
Teacher quality is the teacher who has the ability to realize the goals of national education which has a pedagogical competence, personal competence, social competence and professional competence. Autism is a developmental disorder of behavior and talk so they were not able to hold social interaction and living in his own world. Inclusive education is a key method for dealing with children with autistic disorder. The basic principle of inclusive education is all children should have the opportunity to learn together with normal student. Qualitative research is research that aims to understand the phenomenon of what is experienced by the subjects of the study such behavior, perception, motivation and action in a holistic manner and to describe in words and language in a naturally specific context and by utilizing a variety of natural methods. Behavior of students with autism are basically all the same dipend on the difference in rates of autism symptoms. After that, the behavior of students with autism will be directed to behavior that reflects Islamic religion, such as acting polite against teachers, respect to teachers and adhere to what was ordered by the teacher. Second, the learning achievement of Islamic religious education that has been achieved quite encouraging students with autism. This achievement is evidenced by the completion of the subjects of Islamic religious education in accordance with the standards established school graduation and some non-academic achievements.